The charge : activating the 10 human drives that make you feel alive - Burchard, Brendon (New York : Free Press, 2012)
In the hyper-connected, hyper-digitized world in which we are living, the time has come to revise Abraham Maslow's classic "hierarchy of needs"--a pyramid of human drives that places the basic needs of safety and sustenance at the bottom. Burchard, a world-renowned motivational speaker and bestselling author, makes a compelling case that it's time for an entirely new approach to understanding what drives human ambition and achievement today; it's time to change the conversation about what it takes to succeed and feel alive and fulfilled in a stressful, chaotic, distracted world. In The Charge: Activating the 10 Human Drives that Make You Feel Alive, Burchard, using pioneering studies from the fields of positive psychology and neuroscience, as well as great stories from his own experience, identifies the ten simple drives of human emotion and happiness: Control, Competence, Congruence, Caring, Connection, Change, Challenge, Creative expression, Contribution, and Consciousness. The Charge provides the keys to understanding and activating these drives in clear and concrete ways that will inspire and help everyone find the one thing we all are searching for: more life in our lives.
Out of the darkness -- The five baseline drives -- The drive for control -- The drive for competence -- The drive for congruence -- The drive for caring -- The drive for connection -- The five forward drives -- Introducing the forward drives -- The drive for change -- The drive for challenge -- The drive for creative expression -- The drive for contribution -- The drive for conciousness.
Includes index.
Keywords: Motivation (Psychology)